Desarrollo de una técnica de biorremediación para el tratamiento de agua residual proveniente de la recuperación de oro - Harlyn Ruperto, Rivera Ortiz (2018)
The effluents generated in mining activity contain very high amounts of heavy metals and cyanide, which implies an impact on water sources, the direct discharge of contaminated effluents to water bodies is one of these. In this context, knowing that the treatments and technological methods that are used in the recovery of cyanide represent a high cost of investment has raised the present investigation. There are different types of bioremediation that treat wastewater from various activities, but there are no studies of bioremediation for water contaminated with cyanide from mining activity, it is for this reason that the present investigation has as its purpose the development of a technique of bioremediation for the treatment of residual water from the recovery of gold through the use of native plants (Cecropia peltata l. and Malva sylvestris) Posing alternatives economically viable and environmentally sound with biological treatments, which are friendly to the environment. In this sense, two types of tests with plants, using the crushed and alcoholic extraction in the middle. With crushed after a rest of 5 days between crushed and water with concentration of 0.1 mg/l with both plants obtained a percentage of removal of 17% with the Malva sylvestris and Cecropia peltata l, 12%. In contrast to the testing of dosage is obtained percentages of 14% removal and 11% with the aqueous extracts of Malva sylvestris and Cecropia peltata l respectively.